Association of Sexual Debut in Adolescents With Microbiota and Inflammatory Markers. Issue 1 (July 2016) - Jespers, Vicky; Hardy, Liselotte; Buyze, Jozefien; Loos, Jasna; Buvé, Anne; Crucitti, Tania
Abstract : OBJECTIVE: To investigate the association of sexual debut and vaginal, anorectal, and oral microbiota and vaginal inflammatory markers in female adolescents. METHODS: We conducted a school-based study in adolescents in Antwerp, Belgium. During three visits over 8 months, participants answered questionnaires and self-collected vaginal, anorectal, and oral swabs. Five Lactobacillus species, Lactobacillus genus, Gardnerella vaginalis, and Atopobium vaginae were quantified; and seven inflammatory markers were measured in the vaginal specimens. In the oral and anorectal specimens, Lactobacillus genus, G vaginalis, and A vaginae were ascertained. RESULTS: Of the 93 adolescents (mean age 16.2 years) at the first visit, 41 (44.1%) had passed sexual debut (penile–vaginal intercourse) and five (5.4%) had sexual experience without passing sexual debut. Having sexual experience at the first visit was not found to be associated with species presence or concentrations (acknowledging an underpowered study because the required sample size was not attained). Modeling the longitudinal data on all girls showed that sexual debut was associated with increased odds of vaginal and anorectal G vaginalis ( P =.021; P =.030) and A vaginae ( P =.041; P =.012) with increments of interleukins (interleukin [IL]-1α P <.001, IL-1β P =.046, IL-8 P =.033) and chemokines (regulated on activation, normal T cell expressed and secreted P <.001; macrophage inflammatory protein-1β P =.040), whereas no difference was seen when modeling (before–after) the girls initiating and girls staying without sexual intercourse. The association of sexual intercourse with IL-1α ( P <.001), IL-1β ( P =.030), and IL-8 ( P =.002) at the first visit was (greater than 70%) mediated by vaginal G vaginalis and A vaginae concentrations. CONCLUSION: Sexual debut in adolescents is associated with an inflammatory vaginal reaction and with the presence of bacterial vaginosis–related species. Strategies preventing the colonization of bacterial vaginosis–related organisms during early sexual debut are urgently needed and may prevent acquisition of sexually transmitted infections including human immunodeficiency virus in early life. Abstract : Sexual debut in adolescence is associated with an inflammatory vaginal status and the presence of bacterial vaginosis–related species.